Measurement of the photon structure function <msubsup is="true">F2γ</msubsup> with the L3 detector at LEP - Dova, María Teresa (2005)
The e+e− → e+e−hadrons reaction, where one of the two electrons is detected in a low polar-angle calorimeter, is analysed in order to measure the hadronic photon structure function <msubsup is="true">F2γ</msubsup>. The full high-energy and high-luminosity data set, collected with the L3 detector at centre-of-mass energies 189 GeV ≼ √s ≼ 209 GeV, corresponding to an integrated luminosity of 608 pb−1 is used. The Q2 range 11 GeV2 ≼ Q2 ≼ 34 GeV2 and the x range 0.006 ≼ x ≼ 0.556 are considered. The data are compared with recent parton density functions.